Prospective interpretation of Covid vaccines. A cross sectional study, Ordu province experience - Bestegül Çoruh Akyol; Bennur Turgut; Murat Doğan İşcanlı; Mervegül Kaya; Soner Çankaya; Özgür Enginyurt (Taylor & Francis Group, 2023)
During the pandemic period, many regulations were made to reduce the spread of the epidemic throughout the country and restrictions were applied. We aimed to interpret the effects of vaccination status, total number of vaccination doses and preferred vaccine type on the prognostic process of the patients we treated inpatients with the diagnosis of Covid-19 in our pandemic service. The present descriptive cross-sectional study was conducted in Ordu, Turkey. One hundred and fifty-two people participated. 80.9% (n = 123) of whom were vaccinated against SARS-Cov-2, and 19.1% (n = 29) were unvaccinated. When the treatment processes of the participants were analyzed in general, it was observed that the clinical condition of the individuals who received at least one dose of BNT162b2 vaccine did not worsen (χ2 = 40.080; p = .011). It was determined that BNT162b2 vaccine was not among the vaccine preferences of the cases who needed to be transferred to the intensive care unit in this process and whose clinical processes resulted in death during follow-up in intensive care or service after intensive care referral (χ2 = 64.417; p = .024). According to these results, our study proves once again the protective role of vaccines against epidemic diseases and their progression.